Integrasi Tipologi Paradigma Sosiologi George Ritzer dan Margaret M. Poloma - Suci Fajarni (Jurnal Sosiologi Agama Indonesia (JSAI), 2020)
Sociology as a science has a variety of paradigms born of social scientists. Some of these are the sociology paradigm according to George Ritzer (which consists of a social facts paradigm, a social definition paradigm, a social behavior paradigm), and a sociology paradigm according to Margaret M. Poloma (consisting of a naturalistic / positivistic paradigm, a humanistic / interpretative paradigm, and a paradigm evaluative). This article aims to integrate between the sociology paradigm according to Ritzer and the sociology paradigm according to Poloma through comparative analysis that refers to paradigm elements consisting of ontological, epistemological, methodological, and axiological dimensions.